Customer incivility, employee emotional exhaustion, and job embeddedness relationship in the Indonesian hospitality sector: The socio-economic status perspective - Deni Gustiawan; Noermijati; Siti Aisjah; Nur Khusniyah Indrawati (Cogent Social Sciences)
This study explores the impact of customer incivility on frontline employees’ job embeddedness in the Indonesian hospitality sector. We also investigate whether emotional exhaustion prevalence mediated, and socio-economic status (SES) moderated the link between customer incivility, emotional exhaustion, and job embeddedness. Data were collected in two stages using an online survey of 192 employees from the hospitality sector in Indonesia. We tested a moderated mediation model using Hayes’ Macro PROCESS version 4.0. Results confirmed that frontline service employees with high levels of uncivil consumer behavior experience have high emotional exhaustion tendencies and low job embeddedness. The findings also reveal that emotional exhaustion partially mediates the relationship between customer incivility and job embeddedness. Moreover, SES mitigates the impact of customer incivility on emotional exhaustion and job embeddedness. A lower level of SES triggers a more substantial effect of customer incivility on exhaustion, whereas a higher SES can reduce the effect of customer incivility on job embeddedness.